Reduced aperture radar signal processing - Chia, Lek Guan (Nanyang Technological University, 2022)
Antenna arrays are an important component of radar systems. Over the years, the increasing adoption of digital signal processing has spurred the development of unconventional array processing techniques. In this thesis, two unconventional topics are investigated.